PHYTOCHEMISTRY, CYTOTOXICITY AND APOPTOSIS STUDIES OF Β-SITOSTEROL-3-O-GLUCOSIDE AND Β -AMYRIN FROM PRUNUS AFRICANA - Maiyo, F.; Moodley, R.; Singh, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Prunus africana is used traditionally in many countries for the treatment of cancer and benign prostate hyperplasia.Materials and methods: In this study, compounds from the leaves and bark of this plant were isolated and tested for theircytotoxicity and apoptosis induction in two human cancer cell lines (hepatocellular carcinoma (HepG2) and colorectal carcinoma(Caco-2)) and a non-cancer cell line (embryonic kidney (HEK293)). GC-MS profiling of the extract was also conducted.Results: Three compounds (β-sitosterol, β-amyrin and β-sitosterol-3-O-glucoside) were isolated and the cytotoxic activity of β-amyrin and β-sitosterol-3-O-glucoside on the HepG2, Caco-2 and HEK293 was determined using the MTT cell viability assay. Bothcompounds had significant cytotoxic activity towards the Caco-2 cell line with IC50 values of 81 μg mL-1 and 54 μg mL-1 for β-amyrin and β-sitosterol-3-O-glucoside, respectively while low cytotoxicity was observed on HepG2 cell lines with IC50 values of 206μg mL-1 and 251 μg mL-1 for β-amyrin and β-sitosterol-3-O-glucoside, respectively. Apoptosis induction in cells was studied usingacridine orange/ethidium bromide dual staining. In both cases, the compounds tested demonstrated selective cytotoxicity towardscancer cells with high apoptosis indices in cells exposed to β-amyrin. Low IC50 values of 156 μg mL-1 and 937 μg mL-1 for β-amyrinand β-sitosterol-3-O-glucoside, respectively, were observed in the HEK293 cell line.Conclusion: This study reveals that the plant is rich biologically active compounds thereby validating its ethno-medicinal use.